Unwelcoming Classroom Climates: The Role of Gender Microaggressions in CTE. Issue 178 (June 2017) - Lester, Jaime; Struthers, Brice; Yamanaka, Aoi
Abstract : This chapter reviews the literature, gender and CTE, classroom climate, and faculty–student interactions and presents results of a qualitative study on gender microaggressions in community college CTE classrooms.